Nanoparticulate Fertilizers Increase Nutrient Absorption Efficiency and Agro-Physiological Properties of Lettuce Plant - Sara G. Abdel-Hakim; Ahmed S. A. Shehata; Saad A. Moghannem; Mai Qadri; Mona F. Abd El-Ghany; Emad A. Abdeldaym; Omaima S. Darwish (Agronomy, 2023)
The extensive use of chemical fertilizers is responsible for numerous environmental problems including low food quality, soil degradation, and toxicity to beneficial living organisms in the soil. Nano-fertilizers (NFs) application may be a promising solution for combat these challenges. The current study focused on the efficiency of applying small amounts of NFs incorporated with conventional nitrogen, phosphorus, and potassium (NPK) fertilizers to reduce the quantities of conventional fertilizers (CFs) in lettuce cultivated in sandy soil. This study evaluated the effect of these incorporations on plant growth, yield, phytochemical accumulation, leaf nutrient, and leaf nitrate. A pot experiment was conducted during the winter seasons of 2020/2021 and 2021/2022 using the following treatments: CF100: 100% CFs, CF75NF25: 75% CFs + 25% NFs, CF50NF50: 50% CFs + 50% NFs, CF25NF75: 25% CFs + 75% NFs, and NF100: 100% NFs (=10% of CFs). Our findings displayed that the CF75NF25 and CF50NF50 treatments recorded the highest plant growth parameter values (plant length, root length, number of leaves, and fresh and dry biomass). The maximum of chlorophyll fluorescence measurements (photosystem II efficiency) were obtained in plants fertilized with CF75NF25, followed by CF50NF50 and CF100. The improvement ratios of photosynthetic pigments (Chlorophyll (Chl) a, b, and total) for CF75NF25 were 23.77, 50, and 23.72% in the first season and 10.10, 51.0, and 24.90% in the second season for Chl a, b, and total, respectively, as compared with the CF100 treatment. A similar tendency was observed for the CF50NF50 treatment. Generally, CF75NF25 significantly raised the content of total phenolic compounds (TPC), total flavonoid content (TFC), and antioxidant activity (AOA) in lettuce plants by 36.09, 47.82, and 40.16% in the first season and by 30.39, 37.53, and 32.43% in the second season, respectively, compared with CF100. In addition, the levels of leaf nutrient content and uptake of N, P, and K were significantly higher in plants fertilized with CF75NF25 compared to the other treatments, whereas CF25NF75 had the lowest values among the different treatments across both seasons for most of the tested traits. The nitrate content in lettuce leaves (NO3−) for both seasons was lower than the acceptable level for human consumption. These results indicate that incorporating a low concentration of NFs into CFs could be a promising strategy to reduce the amount of CFs to 75% or 50% of lettuce NPK requirements without significant adverse effects on the growth and productivity of lettuce plants cultivated in sandy soil.